World employment report 1998-99 : employability in the global economy - how training matters - (:unkn) unknown (My University, 1998)
"The World Employment Report 1998-99 reviews the global employment situation and examines how countries in different circumstances and stages of development can develop the best training strategy and flexible and responsive training systems to address these far- reaching changes. The report presents a close analysis of training systems worldwide and an examination of training strategies for increasing national competitiveness, improving the efficiency of enterprises and promoting women's employment opportunities and enhancing the skills and employability of informal sector (especially at-risk youth, long-term unemployed, older displaced workers and workers with disabilities). The report suggests specific policy reforms for making training more efficient and effective. Given the rapid and continuous pace of change in the demand for new skills, the report concludes that training and lifelong learning need to be given the highest priority. The best results from enhancing the education and skill levels of the work force are achieved in an overall growthpromoting environment and when training decisions are taken in close consultation between government, employers and workers. (author's abstract, IAB-Doku) Der Bericht informiert zum einen in einem einleitenden Teil über die weltweite Arbeitsmarktentwicklung in den letzten Jahren und behandelt zum anderen im Hauptteil verschiedene Aspekte der Berufsbildung (IAB)
Keywords: G 1.2 Arbeitsmarkt; S 1 Stufen der Berufsbildung; G 2.3.1 Arbeitsteilung & -organisation; G 1.3.3.4 Wiedereingliederung; Arbeitswelt; Entwicklung; Bildungssystem; Berufsbildung; Arbeitsmarktpolitik; Berufliche Integration; Frauen; Quantitative Angaben; Welt